Optimization of Digital Marketing for Improving Brand Awareness of Airis Luxury Villa and Spa - I Made Heinz Anggara Sanjaya Putra; Made Roys Ambara; Ni Komang Reditya Wahyuni; Ida Ayu Gde Novita Aryasih; Luh Mita Susanti; Sayu Kadek Meitha Maharani; Nyoman Mastiani Nadra (JURNAL AKADEMISI VOKASI, 2025)
This study explores the optimization of digital marketing strategies to enhance brand awareness of Airis Luxury Villa & Spa, a boutique villa located in South Kuta, Bali. As the hospitality industry becomes increasingly competitive, especially in digital spaces, effective marketing through platforms like Instagram and TikTok has become essential. Despite offering premium services and a unique blend of Balinese architecture with modern comfort, the villa previously lacked a structured and strategic digital marketing approach. Using a qualitative descriptive method, this research involved observation, interviews with 12 purposively selected social media users, and documentation analysis over a five - month period. The findings revealed significant improvements in audience engagement and brand recognition following the implementation of consistent, visually appealing, and culturally enriched digital content. Informants highlighted positive perceptions of the villa’s content, particularly cinematic room tours, spa experiences, and scenic visuals. Suggestions included adding interactive features, behind-the-scenes videos, and integrating Balinese storytelling. The research confirms that emotional storytelling, cultural relevance, and consistent branding are key to ef fective digital marketing. Moreover, the study emphasizes the importance of establishing a dedicated digital marketing team to ensure continuous improvement and trend alignment. This case demonstrates how even small -scale accommodations can successfully st rengthen their online presence and competitiveness through strategic digital marketing. The results of this study offer valuable insights for hospitality businesses aiming to boost visibility, build brand equity, and foster meaningful engagement with potential guests in the digital era.